Into battle - Nix, Garth; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 2001)
"The Dark World is in danger, for the Veil is vulnerable. War is soon to come. On one side are Tal and the Underfolk rebels, struggling valiantly for freedom. On another side are Milla and the Icecarls, preparing to assault the Castle in order to preserve their world. And on a third side lies the most sinister force of all, a force of such power that it could unleash the ultimate destruction"--Cover.
"Lucas books."
G5
Keywords: Imaginary places -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Fantasy fiction; Adventure fiction